Enzyme-linked Immunosorbent Assay (ELISA) From A to Z - Hosseini, Samira (SpringerBriefs in Forensic and Medical Bioinformatics,, 2018)
This book offers comprehensive information on all aspects of ELISA, starting with the fundamentals of the immune system. It also reviews the history of analytical assays prior to the advent of ELISA (enzyme-linked immunosorbent assay) and addresses the materials of choice for the fabrication of the platforms, possible biomolecular interactions, different protocols, and evaluation parameters. The book guides readers through the respective steps of the analytical assay, while also familiarizing them with the possible sources of error in the assay. It offers detailed insights into the immobilization techniques used for protein attachment, as well as methods for evaluating the assay and calculating the key parameters, such as sensitivity, specificity, accuracy and limit of detection. In addition, the book explores the advantages and shortcomings of the conventional ELISA, as well as various approaches to improving its performance. In this regard, merging and integrating other technologies with widely known ELISAs have opened new avenues for the advancement of this immunoassay. Accordingly, the book provides cutting-edge information on integrated platforms such as ELISpot, plasmonic ELISAs, sphere-/bead-based ELISAs, paper-/fiber-based ELISAs and ELISA in micro-devices. .